2013
DOI: 10.1063/1.4775749
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogap state and strong scattering of current carriers by local spin moments as mechanisms for the semiconducting properties of near-stoichiometric iron-vanadium-aluminum alloys

Abstract: New experimental evidence is obtained on the physical nature of the semiconducting properties of Fe 2Àx V 1þx Al alloys with near-stoichiometric (x ¼ 0) compositions. We examine the low-temperature thermal emf of two alloys: one is enriched in vanadium and exhibits a pseudogap in the electron density of states at the Fermi energy, while in the other, which is depleted in vanadium, the scattering of electrons by localized spins has a stronger influence. The experimental temperature dependences of the thermal em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It turned out that pseudogap-related anomalies are observed as well in other kinetic and magnetic characteristics of alloys based on Fe2VAl [13,14,[41][42][43]. In [41], the thermoelectric power α(T) of the Fe1.9V1.1Al compound was studied and it was found that at T < 20 K, a large non-monotonic contribution α(T) is observed, the presence of which can be explained by the existence of a pseudogap near the Fermi level EF. The thermal conductivity and heat capacity of Heusler compounds based on Fe2VAl were studied in [13,14,42].…”
Section: Semiconductor-like Heusler Alloysmentioning
confidence: 96%
“…It turned out that pseudogap-related anomalies are observed as well in other kinetic and magnetic characteristics of alloys based on Fe2VAl [13,14,[41][42][43]. In [41], the thermoelectric power α(T) of the Fe1.9V1.1Al compound was studied and it was found that at T < 20 K, a large non-monotonic contribution α(T) is observed, the presence of which can be explained by the existence of a pseudogap near the Fermi level EF. The thermal conductivity and heat capacity of Heusler compounds based on Fe2VAl were studied in [13,14,42].…”
Section: Semiconductor-like Heusler Alloysmentioning
confidence: 96%
“…1 and 2 and references therein). The Heusler compounds family has more than 1500 alloys which exhibit various functional properties, i.e., magnetocaloric effect, 3,4 unusual thermal, 5,6 thermoelectric 7 and semiconductor [8][9][10] characteristics, properties of half-metallic ferromagnets 11,12,18 and spin gapless semiconductors. 13,14,19 The so-called full and inverse Heusler alloys are studied the most.…”
Section: Introductionmentioning
confidence: 99%